2009
DOI: 10.1007/s00423-009-0567-8
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected findings on laparoscopy for suspected acute appendicitis: a pro for laparoscopic appendectomy as the standard procedure for acute appendicitis

Abstract: Laparoscopic appendectomy should be recommended as standard procedure for acute appendicitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 28 publications
2
24
0
3
Order By: Relevance
“…Therefore, the acceptance for laparoscopic appendectomy can be further increased with the degree of standardization. Most surgeons either use a stapler [11] or a loop [6,12] to close the appendicular stump. The use of a stapler is safe and fast but expensive, while the loop is less expensive but requires an advanced level of laparoscopic training.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the acceptance for laparoscopic appendectomy can be further increased with the degree of standardization. Most surgeons either use a stapler [11] or a loop [6,12] to close the appendicular stump. The use of a stapler is safe and fast but expensive, while the loop is less expensive but requires an advanced level of laparoscopic training.…”
Section: Discussionmentioning
confidence: 99%
“…Fifty-eight laparoscopic appendectomies (70.7%) were performed by surgical trainees (first to fifth year of training, n=7) supervised by one of the abovementioned six board certified surgeons. The surgical procedure followed a standardized protocol as described previously [6]. The procedure only differed from the initial report regarding the closure of the appendicular stump.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that LA has the advantages of fewer wound infections, less pain and faster recovery, especially in obese and elderly patients while resulted in more operating time and hospital costs (2)(3)(4)(5). Other than these advantages, laparoscopic approach offers an additional diagnostic tool at the time of surgery (6) …”
Section: Introductionmentioning
confidence: 99%
“…The technical focus in laparoscopic appendectomy is largely on the treatment of appendiceal stump closure. The majority of surgeons use a stapler 7 or a loop 8 to close the appendiceal stump, but although the stapler is safe and fast, it is expensive. On the other hand, the loop is cheaper but it requires a higher level of laparoscopic training.…”
Section: Introductionmentioning
confidence: 99%